Determinan Pengambilan Keputusan Investasi Saham: Survei Galeri Investasi UIN Raden Fatah Palembang - Indria Putri; Lukita Tripermata; Vhika Meiriasari (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of risk perception, herding, and initial minimum capital in making stock investment decisions at the Investment Gallery of UIN Raden Fatah Palembang. Sampling using the slope formula, the result of the calculation obtained is 94 respondents. This research uses the help of SmartPLS software version 4.0. The results of this study obtained that the first hypothesis and had no effect and the third hypothesis had a positive effect with a P-value of 0.023 <0.005.